2017
DOI: 10.3126/kumj.v13i4.16830
|View full text |Cite
|
Sign up to set email alerts
|

School Teachers’ Knowledge about Epilepsy in Kathmandu Metropolitan City

Abstract: Background

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
4
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 28 publications
(36 reference statements)
1
4
0
Order By: Relevance
“…This finding could be in explained that the educational program was effective and successful in knowledge enhancement that reflected on their attitudes and behavior toward primary school children with epilepsy. This result is in agreement with that of [20], who studied "teachers' knowledge about epilepsy in Kathmandu Metropolitan City." who stated similar result.…”
Section: Discussionsupporting
confidence: 91%
“…This finding could be in explained that the educational program was effective and successful in knowledge enhancement that reflected on their attitudes and behavior toward primary school children with epilepsy. This result is in agreement with that of [20], who studied "teachers' knowledge about epilepsy in Kathmandu Metropolitan City." who stated similar result.…”
Section: Discussionsupporting
confidence: 91%
“…Level of education was considered in 16 studies focusing on knowledge and 10 on attitudes and there was a consistent association between higher level of education and knowledge. A higher level of education was associated with significantly better knowledge in eight studies 27,29,32,34,37,46,13,63 and with better attitudes in two studies 13,54 . Number of years teaching was considered in 13 studies focusing on knowledge and 11 focussing on attitudes.…”
Section: Factors Considered As Possibly Associated With Knowledge/attmentioning
confidence: 90%
“…Number of years teaching was considered in 13 studies focusing on knowledge and 11 focussing on attitudes. Three studies showed a significant positive relationship between number of years teaching and knowledge 24,32,13 and four showed a significant negative relationship 21,29,18,50. Four studies showed a significant positive relationship between numbers of years teaching and attitudes 24,13,58,63 .…”
Section: Factors Considered As Possibly Associated With Knowledge/attmentioning
confidence: 95%
“…The majority of people with epilepsy lack access to proper treatment because around 80% of them live in developing countries. [ 2 3 4 ] Epilepsy comprises the most prevalent neurological disorder during childhood, as it affects around 33 million children worldwide. [ 5 ]…”
Section: Introductionmentioning
confidence: 99%